Loading web-font TeX/Math/Italic

x(2x-2)+(x-1)=0

Simple and best practice solution for x(2x-2)+(x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(2x-2)+(x-1)=0 equation:



x(2x-2)+(x-1)=0
We multiply parentheses
2x^2-2x+(x-1)=0
We get rid of parentheses
2x^2-2x+x-1=0
We add all the numbers together, and all the variables
2x^2-1x-1=0
a = 2; b = -1; c = -1;
Δ = b2-4ac
Δ = -12-4·2·(-1)
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
x_{1}=\frac{-b-\sqrt{\Delta}}{2a}
x_{2}=\frac{-b+\sqrt{\Delta}}{2a}

\sqrt{\Delta}=\sqrt{9}=3
x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-3}{2*2}=\frac{-2}{4} =-1/2
x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+3}{2*2}=\frac{4}{4} =1

See similar equations:

| 6.6y+y+6.5=y-6.7 | | 6x−7=26 | | 4(x+2)−2(x−3)=20 | | (3^2-2^3)^66=x | | 2x−3(2+1)=13 | | 6x+12=15+6x | | 5x+2=10+7x | | -6+(4-4x)-(1-x)=2x-2(x-3) | | 18x-42=6x+12 | | -7a+5+8a=6-25 | | 18-8x=2x-2 | | 2(165/x)-22x=44 | | 2/3x-5/6x=1/x+1 | | 3(t-1)+t=2(t-1) | | 5x+6x-10=9+3x+5* | | 38+x+2+x=180 | | x+2x+45=90 | | 3z-6=z-18 | | 11x-8=x-28 | | √3x-11=x-3 | | √3x-11=x-3 | | ®F=(-50x1.8)+32-50+(®F-32) | | 34.20=7g+3.68 | | -4(-8r=3)=-268 | | -4(-8r=3=-268 | | v+3.84=9.37 | | n/4-7/n=1/4 | | x/2-13=10 | | (5+s)/8=5= | | 3^4x-5=1/27^2x+10 | | -88=-4(7p-6) | | 25x^2+64=289 |

Equations solver categories